An androgenic steroid delivery vector that imparts activity to a non-conventional platinum(II) metallo-drug. - Huxley, M; Sanchez-Cano, C; Browning, M; Navarro-Ranninger, C; Quiroga, A; Rodger, A; Hannon, M (2010)
A range of androgen conjugates with non-conventional platinum(II) complexes have been synthesised with the aim of targeting tumour cells since many display elevated levels of the androgen receptor. The androgenic platinum conjugates are delivered into selected cells with improved efficiency (when compared to their non-steroidal analogues). The act of conjugating an androgen to a platinum(II) complex resulted in synergistic effects between the metallic centre and the steroidal ligand, creating highly potent platinum(II) complexes from the inactive components.